Pengembangan Praktikum Kimia Dasar berbasis Video pada Materi Sistem Periodik Unsur - Zainuddin Muchtar; Siti Rahmah; Fauziyah Harahap; Catur Kurniawan; Nadya Ulfa; Fatayatul Hasniyah; Frandika Arif Chaniago; Mhd. Fadhillah; Junifa Layla Sihombing; Sri Adelila Sari; Moondra Zubir (Edukimia, 2022)
Technological developments change the researchers and educators thinking towards online learning. Various innovations were carried out to support effective online learning which suitable with the student competencies. As there is urgency for carrying practicum activities to achieved Course Learning Achievement (Capaian Pembelajaran Mata Kuliah (CPMK)) for the basic chemistry subject, there is need to make some innovation, which is by making practicum video. It could stimulate students critical thinking because it was presented with visual representations. It could overcome the limitations of space and time and could be used repeatedly. The research type was Research and Development with the Borg and Gall development model. The final product will be disseminated through YouTube platform which is integrated with sipda.unimed.ac.id. Validation results in media design and material aspect showed that the product was declared very valid with an average value of 86.87 percent and 97.92 percent, respectively. Meanwhile, the responses from 30 students showed that the product was very practical with an average score of more than 90 percent and was suitable with learning objectives of the basic chemistry course especially the periodic system of elements.